Two different systematic techniques to find analytical solutions of the (2+1)-dimensional Boiti–Leon–Manna–Pempinelli equation - Melike, Kaplan (Elsevier BV, 2018)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Soliton equations; \((2+1)\)-dimensional Boiti-Leon-Manna-Pempinelli equation; transformed rational function method; exact solutions; Solutions to PDEs in closed form; \(\exp(-\Phi(\xi))\) method; 13. Climate action